A novel JNK is involved in immune response by regulating IL expression in oyster Crassostrea gigas. Issue 79 (August 2018) - Sun, Jiejie; Li, Yinan; Li, Meijia; Liu, Yu; Qu, Chen; Wang, Lingling; Song, Linsheng
Abstract: The c-Jun N-terminal kinase (JNK) is a member of mitogen-activated protein kinases (MAPK) highly conserved from yeast to mammals and participates in regulating many physiological and pathological processes. In the present study, a novel JNK was identified from oyster Crassostrea gigas (designated as Cg JNK) and its biological functions were investigated in response against lipopolysaccharide (LPS) stimulation. The Cg JNK consists of 415 amino acids, which includes a serine/threonine protein kinase (S_TKc) domain with a conserved Thr-Pro-Tyr (TPY) motif. Phylogenetic analysis revealed that Cg JNK shared high similarity with other members of the JNK subfamily. CgJNK mRNA was detected in all the tested tissues and CgJNK mRNA expression levels in hemocytes were significantly up-regulated from 6 to 72 h after LPS stimulation and reached the highest level (16.1-fold, p < 0.01) at 24 h. The phosphorylation level of Cg JNK in C. gigas hemocytes was increased at 2 h after LPS stimulation. The subcellular localization of Cg JNK phosphorylation in hemocytes was analyzed after LPS stimulation, and Cg JNK phosphorylation could be detected in both cytoplasm and nucleus of oyster hemocytes at 2 h post LPS stimulation. Additionally, the interleukins ( Cg ILs) were detected in hemocytes of CgJNK -knockdown oysters. CgIL17-1, CgIL17-2, CgIL17-4 and CgIL17-6 transcripts were decreased significantly in CgJNK -knockdown oysters at 24 h post LPS stimulation. In summary, these results suggested that Cg JNK played an important role in the immune response of oysters by regulating IL expression. Highlights: Cg JNK in oyster was involved in immune response against LPS stimulation. Cg JNK expression could be significantly up-regulated from 6 to 72 h after LPS injection. Cg JNK phosphorylation was significantly induced by LPS stimulation. Cg JNK regulated the IL17-1, IL17-2, IL17-4, IL17-6 expression after LPS injection.